Detection of Salmonella and Escherichia coli in Egg Shell and Egg Content from Different Housing Systems for Laying Hens - Loongyai , Wiriya; Wiriya, Benjamaporn; Sangsawang, Naruemol (International Journal of Poultry Science, 2011)
Polymerase Chain Reaction (PCR) assay and conventional microbiological methods were used to detect bacterial contamination of egg shells and egg content in different commercial housing systems, the open house and evaporative cooling systems. A PCR assay was developed for direct detection using a set of primers specific for the invasion by invA gene for Salmonella and uidA gene, encoding β-glucuronidase for Escherichia coli. PCR detected the presence of Salmonella in 2 (5%) samples of egg shells from the evaporative cooling system, while conventional cultural methods detected no Salmonella from the same samples. No Salmonella was detected from the open house system. The frequency of PCR positive samples for E. coli was 35% (16/40) isolated from the open house system and 42% (16/38) from the evaporative cooling system. Two samples screened for E. coli in egg content was also detected by PCR. In comparison, detection of E. coli by culture, done simultaneously with PCR, was 17.5% (7/40) sensitive in the open house system and 31.5% (12/38) sensitive in the evaporative cooling system. Results indicated that this PCR procedure is a sensitive method for Salmonella and E. coli detection. The contamination of Salmonella and E. coli was found at a high frequency in the evaporative cooling system compared with the open house system.